A Method for En Face OCT Imaging of Subretinal Fluid in Age-Related Macular Degeneration - Fatimah Mohammad; Justin Wanek; Ruth Zelkha; Jennifer I. Lim; Judy Chen; Mahnaz Shahidi (Journal of Ophthalmology)
Purpose. The purpose of the study is to report a method for en face imaging of subretinal fluid (SRF) due to age-related macular degeneration (AMD) based on spectral domain optical coherence tomography (SDOCT). Methods. High density SDOCT imaging was performed at two visits in 4 subjects with neovascular AMD and one healthy subject. En face OCT images of a retinal layer anterior to the retinal pigment epithelium were generated. Validity, repeatability, and utility of the method were established. Results. En face OCT images generated by manual and automatic segmentation were nearly indistinguishable and displayed similar regions of SRF. En face OCT images displayed uniform intensities and similar retinal vascular patterns in a healthy subject, while the size and appearance of a hypopigmented fibrotic scar in an AMD subject were similar at 2 visits. In AMD subjects, dark regions on en face OCT images corresponded to reduced or absent light reflectance due to SRF. On en face OCT images, a decrease in SRF areas with treatment was demonstrated and this corresponded with a reduction in the central subfield retinal thickness. Conclusion. En face OCT imaging is a promising tool for visualization and monitoring of SRF area due to disease progression and treatment.